SUMBANGAN PEMIKIRAN JACQUES DUPUIS BAGI HIDUP MENGGEREJA DALAM MASYARAKAT PLURALISTIK - Hardjuna Dhimas Hardjuna (Jurnal Teologi (Journal of Theology), 2017)
Jacques Dupuis understands, in his Trinitarian Christological approach, that every person within his/her historical context, including the context of his/her religious tradition, due to the work of the Holy Spirit, takes part in the salvific work of God which manifests through His Word, which became man in the person of Jesus. Every person who lives religiously within the context of his/her tradition can genuinely acquire supernatural faith as a response to Gods self-manifestation. Moreover, a Trinitarian Christology perspective understands Christocentrism-theocentrism and Christocentrism-regnocentrism not as contradictory, but as complementary. Thus, a Trinitarian Christology perspective understands Christians and believers of other religions as common members of the Kingdom of God. Christians and other religious followers, in their own religious traditions, are all invited to orient their whole lives based on their faith in God. All are invited to establish the Kingdom of God on earth. Such is the vocation of Christians, that is to enter and to participate in the salvific dynamic of the Trinitarian God, who shares their life with others and offers happiness to the whole human race.